Endotracheal Intubation Using the Macintosh Laryngoscope or KingVision Video Laryngoscope during Uninterrupted Chest Compression - Gaszynska, Ewelina (Hindawi Publishing Corporation, 2014)
Objective. Advanced airway management, endotracheal intubation (ETI), during CPR is more difficult than, for example, during anesthesia. However, new devices such as video laryngoscopes should help in such circumstances. The aim of this study was to assess the performance of the KingVision video laryngoscopes in a manikin cardiopulmonary resuscitation (CPR) scenario. Methods. Thirty students enrolled in the third year of paramedic school took part in the study. The simulated CPR scenario was ETI using the standard laryngoscope with a Macintosh blade (MCL) and ETI using the KingVision video laryngoscope performed during uninterrupted chest compressions. The primary endpoints were the time needed for ETI and the success ratio. Results. The mean time required for intubation was similar for both laryngoscopes: 16.6 (SD 5.11, median 15.64, range 7.9–27.9) seconds versus 17.91 (SD 5.6, median 16.28, range 10.6–28.6) seconds for the MCL and KingVision, respectively (P = 0.1888). On the first attempt at ETI, the success rate during CPR was comparable between the evaluated laryngoscopes: P = 0.9032. Conclusion. The KingVision video laryngoscope proves to be less superior when used for endotracheal intubation during CPR compared to the standard laryngoscope with a Mackintosh blade. This proves true in terms of shortening the time needed for ETI and increasing the success ratio.